KARAKTERISTIK, KLASIFIKASI TANAH, DAN PERTUMBUHAN TANAMAN JATI (Tectona grandis Linn f.) Var. UNGGUL NUSANTARA DI CIAMPEA, KABUPATEN BOGOR - - Widiatmaka; Akhmad Mediranto; Hermanu Widjaja (Graduate School Bogor Agricultural University (SPs IPB), 2015)
Teak (Tectona grandis Linn f.) produce one of the most desirable wood in the world. Nowadays, fast growing teak resulting from genetically engineered teak have been available. This study aims to look at the relationship between land characteristics and soil classification with vegetative growth of “Unggul Nusantara” varieties of teak. The study was conducted in Ciampea, Bogor Regency. Soil properties were analyzed from three profiles, while the vegetative growth of teak was measured from 2.5-3 years old teak planted on those land. The diversity of soil properties on the profiles were function of the difference of soil parent material as well as its position on the slopes. Three soil profiles of P-1, P-2, and P-3, lying from upslope to the downslope, were classified respectively as Typic Paleudalf, very fine, mix, active, isohipertermic; Typic Dystrudept, very fine, mix, active, isohipertermic; and Typic Hapludult, very fine, mix, semi-active, isohipertermic. Soil of the three profiles were capable of supporting the growth of teak varieties of “Unggul Nusantara”. The best grown plant was found on the profile P-1 in the upslope, followed by the plant on the profile P-3 in the downslope, and then the plants on land above the P-2 in the middle slope. Nevertheless, the quality of the teak harvest produced in the three profiles can be categorized as low category. Soil with lime sediment parent material that has a high pH and base saturation is able to provide better growth for plants teak varieties of “Unggul Nusantara”. Keywords: soil profile, slope, soil chemical and soil physical characteristics, vegetative performance